2011
DOI: 10.1007/s13369-011-0092-2
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Prime Near-Ring Modules

Abstract: We introduce the notion of a strongly prime near-ring module and then characterize strongly prime near-rings in terms of strongly prime modules. Furthermore, we define a T -special class of near-ring modules and then show that the class of strongly prime modules forms a T -special class. T -special classes of strongly prime modules are then used to describe the strongly prime radical. Basic ConceptsA (right) near-ring is a triple (N , +, ·) such that (N , +) is a group (not necessarily abelian), (N , ·) is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Juglal et.al [7] studied different prime N-ideals and prime relations between generalized matrix nearring and multiplication modules over a nearring. Further, Juglal and Groenewald [8] studied the class of strongly prime nearring modules and shown that it forms a -special class. In Bhavanari and Kuncham [9], the relation between the ideals of the N-group N and the ideals of M n (N)-group N n has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Juglal et.al [7] studied different prime N-ideals and prime relations between generalized matrix nearring and multiplication modules over a nearring. Further, Juglal and Groenewald [8] studied the class of strongly prime nearring modules and shown that it forms a -special class. In Bhavanari and Kuncham [9], the relation between the ideals of the N-group N and the ideals of M n (N)-group N n has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, even a near ring is a zero symmetric near ring, an R-subgroup may not be an ideal. Then K is a zero symmetric near ring, {e} is the only one ideal of K and {e, b} is an R-subgroup of K, see [9]. Therefore, {e, b} is an R-subgroup of K but is not an ideal of K even K is a zero symmetric near ring.…”
Section: Thenmentioning
confidence: 99%